Spelling and Meaning of Compounds in the Early School Years through Classroom Games: An Intervention Study - Tsesmeli, Styliani N. (Frontiers in Psychology, 2017)
The study aimed to evaluate the intervention effects on spelling and meaning of compounds by Greek students via group board games in classroom settings. The sample consisted of 60 pupils, who were attending the 1st and 2 nd grade of two primary schools in Greece. Each grade-class was divided into an intervention (N=29 children) and a control group (N=31 children). Before intervention, groups were evaluated by standardized tests of reading words/ pseudowords, spelling words and vocabulary. Students were also assessed on compound knowledge by a word analogy task, a meaning task and a spelling task. The experimental design of the intervention included a pre-test, a training program and a post-test. The pre- and post-assessments consisted of the spelling and the meaning tasks entailing equally morphologically transparent and opaque compounds. The Training Program was based on word families (N=10 word families, 56 trained items, 5 sessions) and aimed to offer instruction of morphological decomposition and meaning of words. The findings showed that training was effective in enhancing the spelling and most notably the meaning of compounds. A closer inspection of intervention data in terms of morphological transparency, revealed that training group of 1st graders improved significantly both on transparent and opaque compounds, while the degree of gains was larger on opaque items for the 2nd graders. These findings are consistent with the experimental literature and particularly optimistic for the literacy enhancement of typically developing children in regular classrooms.